Anaerobic Membrane Bioreactors for water reuse using municipal wastewater: the role of post-treatment - Huang, Yu (Cranfield University, 2022)
Anaerobic Membrane Bioreactors (AnMBRs) are seen as a promising alternative to Aerobic Membrane Bioreactor (AeMBR) based water reuse schemes as they better support a circular economy paradigm with the potential for recovery of energy and nutrients. However, evidence of their application for water reuse is very limited which significantly restricts their potential deployment. This research aimed to identify the current challenges of using AnMBRs for water reuse with respect to their ability to achieve the quality requirements in state of the art national and regional standards. The work investigates the performance and feasibility of technologies commonly applied as a post-treatment stage for AeMBRs and ultimately to provide references for possible treatment trains for future water reuse implementations. A critical review and controlled pilot scale AnMBR and AeMBR operations followed by lab-scale post-treatment trials were conducted to understand the performance of the investigated post-MBR processes and their potential role in AnMBR based water reuse applications. The distinctive matrices of AnMBR and AeMBR effluents, in particular the different nitrogen species as ammonia in the AnMBR effluent and nitrate in the AeMBR effluent, were found to influence different performance across the investigated post-MBR technologies. The presence of ammonia caused a higher membrane fouling and a potential failure to meet the standard for potable reuse during the RO filtration of the AnMBR effluent. When chlorinated, the AnMBR effluent provided a controllable residual ammonia and chlorine concentration while exhibiting lower disinfection by-products formation potential compared to the AeMBR effluent. UV/TiO₂ delivered a selective removal of organic and nutrient compounds as a function of varying the UV intensity and TiO₂ dose from the AnMBR effluent. These findings highlight the potential to combine these processes to achieve more sustainable treatment trains producing high quality effluents for various water reuse applications. In particular, the combination of AnMBR-Chlorination shows promise as a circular economy approach to municipal wastewater treatment for agriculture irrigation.
Jeffrey, Paul - Associate Supervisor
Keywords: Anaerobic membrane bioreactor (AnMBR); Sustainable wastewater treatment; Standards; Agriculture irrigation; Indirect potable water reuse (IPR); Reverse osmosis (RO); Disinfection by-products (DBPs); UV/TiO2; Treatment train